Immunomodulatory properties of Brucella melitensis lipopolysaccharide determinants on mouse dendritic cells in vitro and in vivo. Issue 1 (1st January 2018) - Zhao, Yun; Hanniffy, Sean; Arce-Gorvel, Vilma; Conde-Alvarez, Raquel; Oh, SangKon; Moriyón, Ignacio; Mémet, Sylvie; Gorvel, Jean-Pierre
ABSTRACT: The lipopolysaccharide (LPS) is a major virulence factor of Brucella, a facultative intracellular pathogenic Gram-negative bacterium. Brucella LPS exhibits a low toxicity and its atypical structure was postulated to delay the host immune response, favouring the establishment of chronic disease. Here we carried out an in-depth in vitro and in vivo characterisation of the immunomodulatory effects of Brucella LPS on different dendritic cell (DC) subpopulations. By using LPSs from bacteria that share some of Brucella LPS structural features, we demonstrated that the core component of B. melitensis wild-type (Bm-wt) LPS accounts for the low activation potential of Brucella LPS in mouse GM-CSF-derived (GM-) DCs. Contrary to the accepted dogma considering Brucella LPS a poor TLR4 agonist and DC activator, Bm-wt LPS selectively induced expression of surface activation markers and cytokine secretion from Flt3-Ligand-derived (FL-) DCs in a TLR4-dependent manner. It also primed in vitro T cell proliferation by FL-DCs. In contrast, modified LPS with a defective core purified from Brucella carrying a mutated wadC gene (Bm- wadC ), efficiently potentiated mouse and human DC activation and T cell proliferation in vitro . In vivo, Bm-wt LPS promoted scant activation of splenic DC subsets and limited recruitment of monocyte- DC like cells in the spleen, conversely to Bm- wadC LPS. Bm- wadC live bacteria drove high cytokine secretion levels in sera of infected mice. Altogether, these results illustrate the immunomodulatory properties of Brucella LPS and the enhanced DC activation ability of the wadC mutation with potential for vaccine development targeting Brucella core LPS structure.